A systematic review of living lab literature - Hossain, Mokter; Leminen, Seppo; Westerlund, Mika (Journal of Cleaner Production, 2019)
A living lab is a physical or virtual space in which to solve societal challenges, especially for urban areas, by bringing together various stakeholders for collaboration and collective ideation. Although the notion has received increasing attention from scholars, practitioners and policy makers, its essence remains unclear to many. We therefore performed a systematic literature review of a sample of 114 scholarly articles about living labs to understand the central facets discussed in the nascent literature. In particular, we explored the origin of the living lab concept and its key paradigms and characteristics, including stakeholder roles, contexts, challenges, main outcomes, and sustainability. While doing this, we discovered that the number of publications about living labs has increased significantly since 2015, and several journals are very active in publishing articles on the topic. The living lab is considered a multidisciplinary phenomenon and it encompasses various research domains despite typically being discussed under open and user innovation paradigms. What is more, the existing literature views living labs simultaneously as landscapes, real-life environments, and methodologies, and it suggests that they include heterogeneous stakeholders and apply various business models, methods, tools and approaches. Finally, living labs face some challenges, such as temporality, governance, efficiency, user recruitment, sustainability, scalability and unpredictable outcomes. In contrast, the benefits include tangible and intangible innovation and a broader diversity of innovation. Based on our analysis, we provide some implications and suggestions for future research.
Keywords: Innovation ouverte; Living labs; Revue de littérature; Sustainability